STUDI PRELIMINARI TENTANG PENGARUH D-GALAKTOSA DALAM MENGINDUKSI STRES OKSIDATIF PADA MENCIT JANTAN GALUR OUTBRED FK USU - Bintang, Siti Sarah Bintang Sarah; Siregar, Yahwardiah; Ichwan, Muhammad (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Abstract Oxidative stress occurs due to imbalance of free radicals over antioxidant level in the body. This condition causes lipid peroxidation and DNA damage. D-Galaktosa is The mechanism of oxidative stress induced by d-galactose occurs in the subcellular, especially in the brain's mitochondria. Increasing the concentration of d-galaktosa is oxidized by galaktosa oxidase to form hydrogen peroxide (H202) which causes a decrease in superoxide dismutase (SOD). H202 reacts with reduced iron and forms hydroxide ions (OH-). Objective: The aim of this study was to determine the effect of d-galaktosa induction on oxidative stress levels (MDA) in male mice. Methods: Methods of samples of mice given d-galaktosa and blood collection from the heart were carried out at the Pharmacology Laboratory of the Faculty of Medicine, University of North Sumatra. Results: The results showed that administration of d-galaktosa, through intraperitonial injection every day for 6 weeks, had an effect on the levels of oxidative stress in male mice. Conclusion: The results of this study indicate that administration of d-galaktosa, through intraperitonial injection every day for 6 weeks, has an effect on levels of oxidative stress in male mice.